The current status of genetic monitoring in conservation introductions - Elspeth A. McLennan; Catherine E. Grueber; Katherine Belov; Carolyn J. Hogg (Conservation Science and Practice)
Abstract Conservation introductions, translocating species beyond their native range, are increasingly necessary. Because genetic diversity is essential for species to respond to novel environments, understanding whether establishing populations can maintain genetic diversity is crucial to the long‐term success of conservation introductions. Using a systematic review, we quantified conservation introductions globally and assessed whether genetic monitoring is occurring. We found that, despite extensive discussion, conservation introductions were rare. Of 167 examples, most were performed in North America, Australia, and China, with megadiverse developing nations underrepresented. Plants were disproportionately represented (74%), and climate change was the primary motivator of conservation introductions (40%). Survival and reproduction were the most frequently measured outcomes (71% and 37%, respectively). Ten works (5.9%) reported genetic monitoring, of which only two considered temporal genetic data and showed a worrying trend of rapid negative genetic change post‐establishment. With limited genetic evidence, it remains unclear whether conservation introductions can establish self‐sustaining populations. As these translocations may be the only option for some species, we recommend conservation practitioners trial conservation introductions with temporal genetic monitoring to assess the maintenance of founding genetic diversity and inbreeding. Only through scientifically derived applications of conservation introductions will we learn how to establish self‐sustaining populations in an uncertain future.